Metabolism of carotenoid pigments and Vitamin A by swine. Provitamin A from alfalfa and yellow corn and gelatin-stabilized Vitamin A as sources of Vitamin A for weanling pigs. - Parrish, D.B.; Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
There is relatively little information on the utilization of vitamin A of different sources by weanling pigs. In this test, three sources of vitamin A were used: (1) a gelatin-stabilized vitamin A product, (2) carotene as supplied by high-quality alfalfa meal, and (3) carotene and cryptoxanthin as supplied by yellow corn. Alfalfa and yellow corn were analyzed for carotene and crude cryptoxanthin and units of vitamin A calculated by multiplying micrograms of these carotenoid pigments by 1.6 and 0.8, respectively.
Keywords: Swine; Vitamin A; Carotene; Corn